Mineralization of 4-fluorocinnamic acid by a Rhodococcus strain - Amorim, Catarina L. (2014)
A bacterial strain capable of aerobic degradation of 4-fluorocinnamic acid (4-FCA) as the sole source of carbon and energy was isolated from a biofilm reactor operating for the treatment of 2-fluorophenol. The organism, designated as strain S2, was identified by 16S rRNA gene analysis as a member of the genus Rhodococcus. Strain S2 was able to mineralize 4-FCA as sole carbon and energy source. In the presence of a conventional carbon source (sodium acetate [SA]), growth rate of strain S2 was enhanced from 0.04 to 0.14 h−1 when the culture medium was fed with 0.5 mMof 4- FCA, and the time for complete removal of 4-FCA decreased from 216 to 50 h.When grown in SA-supplemented medium, 4-FCA concentrations up to 1 mM did not affect the length of the lag phase, and for 4-FCA concentrations up to 3 mM, strain S2 was able to completely remove the target fluorinated compound. 4-Fluorobenzoate (4-FBA) was transiently formed in the culture medium, reaching concentrations up to 1.7 mM when the cultures were supplemented with 3.5mMof 4-FCA. Trans,trans-muconate was also transiently formed as a metabolic intermediate. Compounds with molecular mass compatible with 3-carboxymuconate and 3-oxoadipate were also detected in the culture medium. Strain S2 was able to mineralize a range of other haloorganic compounds, including 2- fluorophenol, to which the biofilm reactor had been exposed. To our knowledge, this is the first time that mineralization of 4-FCA as the sole carbon source by a single bacterial culture is reported.